Internet Legislation: Russian and International Experience - A. S. Ageychev (Сравнительная политика, 2016)
Today Russia is often being criticized for new legislative initiatives in the field of Internet communications. Laws in this area are often negatively perceived by online community and critics and are the cause of misunderstanding between the government and society. Russia, however, is not the only country that has attempted to regulate its online sphere. World practice shows that many states are seeking to regulate virtual life of society. Such initiatives are indeed useful and necessary. The world today is shifting to a new reality where virtual space will play an increasingly important role, but it will raise many dangers and challenges that are needed to be solved at the legislative level. The regulation of the Internet is at the junction of legislation and politics as it is directly concerns the interests of society, the rights and freedoms of the individual, so it is impossible to resolve these problems in isolation from political science and sociology. This article contains a brief review of the legislation in the field of Russian Internet and in some countries, and represents an attempt to determine a necessary level of government intervention in the Internet and the level of its regulation.